Kesiapan dalam Implementasi Kurikulum Merdeka Belajar - Rahmi Ali; La Ode Amaluddin; La Ode Nursalam; La Harudu (Jurnal Penelitian Pendidikan Geografi, 2024)
Curriculum and teachers cannot be separated from each other because teachers have a big role in the success or failure of implementing the curriculum. The aim of this research is to determine teacher readiness in implementing the merdeka curriculum as well as the supporting and inhibiting factors faced by schools in implementing the merdeka belajar curriculum. This type of research is descriptive with mixed methods, combining qualitative and quantitative. Data collection techniques used questionnaires and interviews. The subjects in this research were all class X teachers who implemented the merdeka belajar curriculum, totaling 31 teachers. The data analysis technique uses descriptives in the form of percentages The results of the study show that the readiness of Senior High School 1 Pasarwajo teachers in implementing the merdeka belajar curriculum is in the "Very Ready" category of 6.45% (2 teachers), "Ready" category of 25.81% (8 people), "Quite Ready" category of 45.16% (14 teachers), the "Not Ready" category of 16% (5 people) and the "Very Not Ready" category of 6.45% (2 teachers). Based on the results above, the readiness of Senior High School 1 Pasarwajo teachers in implementing the merdeka belajar curriculum is in the "Quite Ready" category.